2020
DOI: 10.1097/tgr.0000000000000275
|View full text |Cite
|
Sign up to set email alerts
|

Boxing Exercises as Therapy for Parkinson Disease

Abstract: A noncontact boxing program called “Rock Steady Boxing” (RSB) is a popular exercise option for people with Parkinson disease (PD). This retrospective observational study assessed the impact of RSB on clinically relevant outcome measures in 62 PD patients. The change from program beginning to completion in the 30-second sit-to-stand (STS) test, the Timed Up and Go (TUG) test, a quality-of-life survey (the EQ-5D), and a satisfaction survey was analyzed. Significant improvement was observed in the STS and TUG tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…All studies obtained 60% or more of the total scale score for randomised (32 points) and non-randomised (17 points) controlled trials, as shown in Table 1. Two studies obtained a score of 28/32 (Combs et al, 2013;Ciaccioni et al, 2019), one of 27/32 (Jansen et al, 2017), three of 14/17 (Marie-Ludivine et al, 2010;Dawson et al, 2020;Fleisher et al, 2020), and one of 11/17 (Lantheaume et al, 2017), indicating a moderate to high methodological quality, so no studies were excluded from the systematic review.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…All studies obtained 60% or more of the total scale score for randomised (32 points) and non-randomised (17 points) controlled trials, as shown in Table 1. Two studies obtained a score of 28/32 (Combs et al, 2013;Ciaccioni et al, 2019), one of 27/32 (Jansen et al, 2017), three of 14/17 (Marie-Ludivine et al, 2010;Dawson et al, 2020;Fleisher et al, 2020), and one of 11/17 (Lantheaume et al, 2017), indicating a moderate to high methodological quality, so no studies were excluded from the systematic review.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Eight studies were excluded because they were not OCS interventions; seven for not having HRQoL measurements; nine because the mean age of the sample was <45 years of age; eight because they did not correspond to the research object (i.e., not centred on the HRQoL outcomes of adults 45 years and older); four for not being able to access the full texts of the studies; and four because they were reviews or case studies. After this process, seven studies met the selection criteria (Marie-Ludivine et al, 2010;Combs et al, 2013;Jansen et al, 2017;Lantheaume et al, 2017;Ciaccioni et al, 2019;Dawson et al, 2020;Fleisher et al, 2020).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relatively recent development of community-based exercise programs for people with chronic neurological conditions represents a positive shift in the field towards addressing the need for long-term, affordable motor rehabilitation services. Of note, some existing community-based programs, mainly targeted to people with chronic stroke, already utilize instructors with skillsets consistent with kinesiologist training [ 47 52 ]. Here, we highlight two programs developed in Canada: Together in Movement and Exercise (TIME™) [ 49 ] and the Fitness and Mobility Exercise (FAME) Program [ 50 ].…”
Section: Kinesiologists and Chronic Neurological Motor Rehabilitationmentioning
confidence: 99%